2022
DOI: 10.3390/healthcare10071250
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of Implants with Implant-Supported Fixed Dental Prostheses in the Elderly Population: A Retrospective Study with a 5- to 10-Year Follow-Up

Abstract: This retrospective study aimed to investigate the survival rate of implants from 5 to 10 years after the placement of implant-supported fixed dental prostheses (ISFDPs) and the management of implant loss in the elderly population. Elderly patients (≥65 years old) who had been treated with ISFDPs and followed up with for at least 5 years between October 2009 and March 2020 were enrolled. Patient profiles and implant-related data were extracted. The survival rate of implants up to 5 years as well as the 10-year … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…However, the results of the present meta-analysis showed that in terms of the survival rate of teeth, narrow implants did not have a statistically significant difference with standard implants and they were almost equal in terms of the survival rate. The use of small diameter implants in edentulous areas with low bone width or a reduced mesiodistal space is considered to be a suitable treatment option compared with ridge widening treatments because it is simpler and less expensive (30)(31)(32). On the other hand, using implants with a small diameter, in addition to solving the patient's need for bone width surgery, provides acceptable beauty by delivering the prosthesis to the patient on the day of the surgery (especially if the toothless area is in the anterior) (33).…”
Section: Discussionmentioning
confidence: 99%
“…However, the results of the present meta-analysis showed that in terms of the survival rate of teeth, narrow implants did not have a statistically significant difference with standard implants and they were almost equal in terms of the survival rate. The use of small diameter implants in edentulous areas with low bone width or a reduced mesiodistal space is considered to be a suitable treatment option compared with ridge widening treatments because it is simpler and less expensive (30)(31)(32). On the other hand, using implants with a small diameter, in addition to solving the patient's need for bone width surgery, provides acceptable beauty by delivering the prosthesis to the patient on the day of the surgery (especially if the toothless area is in the anterior) (33).…”
Section: Discussionmentioning
confidence: 99%